Exploring the Causes and Management of Dental Implant Failures- A Review - Selvaraj, Teena; Mahendra, Jaideep; Bedi, Muskan; Namasivayam, Ambalavanan (International Journal Of Drug Research And Dental Science, 2024)
Background: Osseointegrated dental implants have been considered the most esthetical and functional alternative to missing teeth. However, the treatment is not always successful resulting in implant loss. The implant loss can be attributed to factors such as biological, microbiological, and biomechanical, but the cause and mechanism of the early implant failure are still obscure. Dental implant failure has led to continuous innovations of various implant systems and to different interceptive treatment modalities. These concerns have also led to the selection of implant designs that best suit the various types of bone. There are a variety of reasons for the failure of endosseous implants. Different reasons for implant failure and their contributing factors have been discussed in the review article.Materials and Methods: Failure of dental implants has been the subject of a comprehensive electronic literature search from 2003 to 2023 using PubMed and Google Scholar databases with relevant MeSH terms and keywords. The causes and management of dental implant failures were used to identify studies for this review. Selected article references were checked to expand the article search.Results: The search strategy yielded 65 titles. Twenty articles that met our inclusion criteria were included in the qualitative analysis. The result shows that the most common type of implant failure is caused either by poor treatment planning or poor surgical execution. To optimize the treatment outcome through dental implants, etiology and factors associated with implant failures should be taken into consideration. Such knowledge is needed for developing adequate treatment and prevention strategies.Conclusion: Identification of the etiology, current condition, and the proper protocol for the various treatment options will reduce the various hitches in implant surgery. Follow-ups and reviews during the osteointegration phase would definitely minimize the post-surgical complications.